2012
DOI: 10.4161/cbt.21785
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic interactions between tumor cells and tumor-associated stroma (TAS) in prostatic cancer

Abstract: Tumor-associated stroma (TAS) is not simply a supporting element for cancer cells, but plays an important role in tumor growth, invasion and metastasis. Changes on the level of stromal constituents, such as loss of Caveolin-1 and increased thymidine phosphorylase (TP) expression, have been associated with tumor aggressiveness. The mutual cooperation between stromal fibroblasts and cancer cells is another distinguishing feature, which has recently emerged. In this investigation, both the loss of Caveolin-1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 22 publications
3
40
1
Order By: Relevance
“…Inhibition of the FAO metabolic pathway has shown promising results for therapy of prostate cancer (10,17), and pharmacological inhibition of FAO sensitizes human leukemic cells to apoptosis (23). In addition, proteins involved in FAO, such as carnitine palmitoyltransferase I, have been shown to have an antiapoptotic function that has been attributed to cross talk with proapoptotic proteins (11,20).…”
Section: Glycolysis Inhibition Results In Enhancement Of Fao Which Imentioning
confidence: 99%
“…Inhibition of the FAO metabolic pathway has shown promising results for therapy of prostate cancer (10,17), and pharmacological inhibition of FAO sensitizes human leukemic cells to apoptosis (23). In addition, proteins involved in FAO, such as carnitine palmitoyltransferase I, have been shown to have an antiapoptotic function that has been attributed to cross talk with proapoptotic proteins (11,20).…”
Section: Glycolysis Inhibition Results In Enhancement Of Fao Which Imentioning
confidence: 99%
“…11 Such an explanation suggests that ADC normalisation may be particularly problematic in a presurgical setting than when applied in men with only clinical suspicion for prostate cancer, given that patients in the former group will generally have undergone more recent biopsies and harbour more aggressive disease that may incite surrounding reactive stromal changes. 12 Such factors can disrupt the ADC of benign areas and hinder the utility of benign prostate tissue as a reference measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Caveolin-1 was strongly associated with the presence of fibroblasts. Although it has been demonstrated that the fibroblast expression of caveolin-1 favors directional migration and invasiveness of carcinoma cells in vitro as well as in vivo, stromal caveolin-1 remodels peri-and intratumoral microenvironments to facilitate tumor invasion, correlating with increased metastatic potency (32,33), current evidence indicates that the increased expression of caveolin-1 in prostate adenocarcinoma cells and the downregulation of the protein in prostate stroma, mediate progression to the castration-resistant phase of PCa (34). CAFs have been reported to promote epithelial-mesenchymal transition in cancer cells, thereby enhancing their aggressiveness and stem-like properties (7,(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%